Analisis Penulisan Teks Akademik pada Jurnal “Pemahaman Materi Pembelajaran dalam Sistem SKS di Sekolah MAN 1 Medan” Oleh Susanti, S. dkk - Mara Untung Ritonga; Salsabila Adnin Daulay; Desy Novita Berutu; Yesi Okta Hutagalung (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze language rules in writing academic texts in the journal Pemahaman Materi Pembelajaran dalam Sistem SKS di Sekolah MAN 1 Medan oleh Susanti, S. et. al. This study focuses on spelling aspects, punctuation, use of capital letters, word selection (diction), sentence structure, use of conjunctions, and writing absorption words. The research method used is descriptive qualitative with data collection techniques through the reading and take a note method. The results showed that the journal had largely met academic language rules, but there were still some mistakes, such as the use of ineffective and redundant sentences, spelling errors and punctuation, as well as the use of inappropriate diction. This error can affect the credibility and ease of readers in understanding the academic text. Therefore, further revision is needed so that the text is more in accordance with the standard writing of academic texts that are good and correct. This research confirms the importance of linguistic rules in academic texts to improve the quality of scientific writing. By understanding and applying the correct writing rules, the author can produce scientific texts that are clearer, systematic, and easy to understand.